(untitled) (Journal of Academic Research, 2025)
This study examines the alignment between skills taught in the translation courses at the English department, Faculty of Arts- Misrata University and the competencies sought by prospective employers. It aims to investigate whether students are adequately prepared for market demands, and aims to bridge the gap between academic outputs and industry needs. Utilizing a quantitative research approach, the study involves prospective employers from various sectors and English department teachers. Structured questionnaires assess required skills, educational gaps, potential areas of collaboration and potential curriculum improvements. Preliminary findings reveal a significant skills gap, especially in practical training and technology use in translation. Prosepctive mployers emphasize the need for graduates to possess practical skills that complement their academic training. On the other hand, teachers express a desire to integrate these competencies and show willingness to work for with prospective employers for better alignment. The study highlights the importance of collaboration between academia and industry to enhance curriculum relevance, better prepare students for careers, and develop strategies to address the education-employment gap, ultimately fostering a more skilled workforce.